Pengaruh Akuntabilitas dan Transparansi terhadap Efektivitas Penggunaan Dana Bantuan Operasional Penyelenggaraan (BOP) pada Pusat Kegiatan Belajar Masyarakat (PKBM) dan Sanggar Kegiatan Belajar (SKB) di Kota Padang - Alfachri Gusva Putra; Fefri Indra Arza; Dian Indah Hayati (Jurnal Eksplorasi Akuntansi, 2026)
To assist the implementation of non-formal education, since 2016 the government has provided Operational Assistance for Education (BOP) Equivalency to the Learning Activity Center (SKB) and Community Learning Activity Center (PKBM) in Padang City. This study aims to determine the influence of accountability and transparency on the effectiveness of the use of BOP funds in SKB and PKBM in Padang City. Quantitative method of multiple linear regression analysis was conducted to analyze the effect of accountability and transparency on the effectiveness of BOP fund usage in SKB and PKBM in Padang City. The results of the study showed that accountability and transparency, both individually and simultaneously, had a positive and significant effect on the effectiveness of BOP fund usage in SKB and PKBM in Padang City. This means that the application of good governance principles, especially accountability and transparency, is very important in improving the quality of non-formal education fund usage such as BOP.”